2007
DOI: 10.1042/bst0351127
|View full text |Cite
|
Sign up to set email alerts
|

Chronic microglial activation and progressive dopaminergic neurotoxicity

Abstract: PD (Parkinson's disease) is characterized by the selective and progressive loss of DA neurons (dopaminergic neurons) in the substantia nigra. Inflammation and activation of microglia, the resident innate immune cell in the brain, have been strongly linked to neurodegenerative diseases, such as PD. Microglia can respond to immunological stimuli and neuronal death to produce a host of toxic factors, including cytokines and ROS (reactive oxygen species). Microglia can also become persistently activated after a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
223
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(227 citation statements)
references
References 60 publications
(76 reference statements)
2
223
0
2
Order By: Relevance
“…Numerous studies have shown evidence of oxidative stress in PD patients and MPTP-treated mice, including high levels of oxidative nucleic acid damage (64,65) and protein oxidation (5,46). The ROS inducing these molecular modifications are generated by microglial NADPH oxidase and play an important role in the development of oxidative stress in the MPTP model of PD (66). Several studies (7,67), including our recent investigations (4,5), have implicated the activation of microglial NADPH oxidase in DA neuron degeneration in SN of MPTP-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown evidence of oxidative stress in PD patients and MPTP-treated mice, including high levels of oxidative nucleic acid damage (64,65) and protein oxidation (5,46). The ROS inducing these molecular modifications are generated by microglial NADPH oxidase and play an important role in the development of oxidative stress in the MPTP model of PD (66). Several studies (7,67), including our recent investigations (4,5), have implicated the activation of microglial NADPH oxidase in DA neuron degeneration in SN of MPTP-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…If the release of these inflammatory and oxidative stress factors becomes chronic, microglia reactivity worsens, causing toxicity in the surrounding area and possibly affecting neighboring neurons. Hypothalamic POMC neurons have been shown to be particularly vulnerable to this reaction (Block & Hong 2007). Microglia are responsive to metabolic neuropeptides, with NPY and αMSH modulating their secretion of cytokines and NO (Delgado et al 1998, Ferreira et al 2011.…”
Section: Microglia In Metabolic Controlmentioning
confidence: 99%
“…Recent reviews have suggested that excessive inflammation may result in DA neuronal loss during the progression of PD (37). Proinflammatory substances such as cyclooxygenase 2 (COX2) and proinflammatory cytokines, including interleukine-1 beta (IL-1β), interferon-gamma (IFN-γ) and tumor necrosis factor-alpha (TNF-α), have been elevated in the postmortem PD brain (38)(39)(40)(41)(42).…”
Section: Involvement Of Glial Activation In Pd Microglial Activation mentioning
confidence: 99%